2018
DOI: 10.1002/ijch.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Electrochemistry

Abstract: Numerous conceptual difficulties and misconceptions have been reported in the science and chemistry education literature about electrochemistry concepts such as electrolytes, redox equations, and about electrochemical (galvanic and electrolytic) cells. Other studies have considered teaching approaches aimed at improving learning and at overcoming misconceptions. This paper reviews these studies and considers strategies and approaches for the effective teaching of electrochemistry. Then, the review focuses on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
3
16
0
2
Order By: Relevance
“…3 The team thereby suggested avenues to reinvigorate electrochemistry education based on today's inexpensive electronics and open-source software providing new tools for teaching electrochemistry interdisciplinary concepts. 3 Similar findings were reported in 2019 by Tsaparlis in Greece noting that electrochemistry was a "hard subject for students" 4 due to complexity and plurality of its concepts. 4 Tsaparlis' study opens with a quotation of Japan's electrochemistry scholar Akiro Yoshino (awarded the Nobel Prize in chemistry in the same year for the development of lithium-ion batteries): 6 "battery technologies are electrochemistry, a complex and difficult interdisciplinary field".…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…3 The team thereby suggested avenues to reinvigorate electrochemistry education based on today's inexpensive electronics and open-source software providing new tools for teaching electrochemistry interdisciplinary concepts. 3 Similar findings were reported in 2019 by Tsaparlis in Greece noting that electrochemistry was a "hard subject for students" 4 due to complexity and plurality of its concepts. 4 Tsaparlis' study opens with a quotation of Japan's electrochemistry scholar Akiro Yoshino (awarded the Nobel Prize in chemistry in the same year for the development of lithium-ion batteries): 6 "battery technologies are electrochemistry, a complex and difficult interdisciplinary field".…”
Section: Introductionsupporting
confidence: 73%
“…3 Similar findings were reported in 2019 by Tsaparlis in Greece noting that electrochemistry was a "hard subject for students" 4 due to complexity and plurality of its concepts. 4 Tsaparlis' study opens with a quotation of Japan's electrochemistry scholar Akiro Yoshino (awarded the Nobel Prize in chemistry in the same year for the development of lithium-ion batteries): 6 "battery technologies are electrochemistry, a complex and difficult interdisciplinary field". 5 Electrochemistry, noted Fergus in 2012, is not typically identified as a separate academic discipline and formal electrochemistry educational programs were still lacking both in the USA and abroad.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Pada konsep sel elektrolisis, mahasiswa dapat menjelaskan bahwa terjadi pergerakan ion menuju elektroda yang sesuai tetapi gagal menjelaskan reaksi redok yang terjadi di elektroda tersebut (Kong, 2016). Lemahnya kemampuan memahami konten elektrokimia dapat disebabkan karena gaya belajar mereka yang masih berpusat pada pembelajaran yang dilakukan di kelas, tidak mencari alternative atau pemahaman sendiri di luar kelas dan tidak membiasakan mengevaluasi kesulitan-kesulitan belajar yang mereka alami (Tsaparlis, 2019).…”
Section: Pendahuluanunclassified
“…Numerous conceptual difficulties and misconceptions regarding electrochemistry concepts such as electrode potential and galvanic and electrolytic cells have been reported in the science and chemistry education literature [2][3][4][5]. Similarly, despite the wide application of electrochemistry in industry and other fields, science ISSN: 2089-9823  South African twelfth grade students' conceptions regarding Electrochemistry (Kwaku Darko Amponsah) 363 teachers [6][7] and students alike [8][9][10][11][12][13] have difficulties with electrochemistry concepts. Correspondingly, alternative conceptions about electrochemistry have also been stated by several studies [14][15][16] which have indicated that electrochemistry can be described as one of the most challenging, problematic as well as demanding sub-disciplines of chemistry [17] since it has so many ambiguous and abstract terms with stated discrepancies and unreasonable representation [14,15,18].…”
Section: Introductionmentioning
confidence: 99%